Frequency and antimicrobial susceptibility of bacterial agents causing peritoneal dialysis-peritonitis in a Brazilian single center over 20 years - Augusto C. Montelli; Terue Sadatsune; Alessandro L. Mondelli; Maria L.R.S. Cunha; Jacqueline C.T. Caramori; Pasqual Barretti; Carlos H. Camargo (Cogent Medicine, 2016)
Peritonitis remains the main complication of peritoneal dialysis (PD). Antimicrobial therapy may be threatened by development of bacterial resistance, demanding continuous surveillance of infectious agents to improve empirical treatment. The aims of this study were to evaluate the bacterial agents causing peritonitis and their antimicrobial susceptibility in patients undergone PD in a Brazilian center, between 1993 and 2013. Strains were recovered from peritoneal fluid, identified by usual methods and submitted to Etest antimicrobial susceptibility. A total of 400 strains were studied, of which 65.8% were Staphylococcus spp.: S. epidermidis, the main species (22.8%), followed by S. aureus (21.3%). Over time, we verified a decrease in overall peritonitis occurrence, and an increase in gram-negative bacteria proportion, attributed, mainly, to a decrease in gram-positive agents. Vancomycin was effective against all Staphylococcus strains, and oxacillin resistance was higher in coagulase-negative Staphylococcus compared to S. aureus (p < 0.01). Regarding gram-negative bacteria, Enterobacteriaceae species accounted for 20.3% of the strains, but P. aeruginosa, Acinetobacter species, S. maltophilia, B. cepacia, P. fluorescens and A. xylosoxidans were also detected (14.3%). Non-fermentative gram-Negative bacilli presented increased antimicrobial resistance compared to Enterobacteriaceae, and imipenem was the most active antimicrobial drug. Over the 20 year period, increasing or decreasing in the antimicrobial susceptibilities were not observed, despite the occurrence of punctual oscillations. In summary, we verified peritonitis occurrence declining over years, gram-positive infections proportion dropping, and, inversely, gram-negative pathogens proportion increasing. Our finding reinforces recommendations regarding retrospective evaluation of antimicrobial susceptibility to define the optimal empirical therapy in each center.